Record of Aspergillus terreus (Thorn.) (Fungi) as fish pathogen - Shrivastava, A K (Indian Journal of Fisheries, 2011)
Aspergillus terreus a fungus found associated with some freshwater fishes namely Channa punctatus, Heteropneustes fossilis and Clarius batrachus cultured in the Gobindgarh tank of Rewa (Madhya Pradesh), India was seen to be pathogenic. The infected fishes showed grey white patches over the body. Haemorrhagic ulceratic patches were observed on the gill and skin. The infections resulted in the death of the fishes